2018
DOI: 10.1039/c8sm01504j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-based complex coacervate core micelles with tuneable supramolecular host–guest, metal-to-ligand and charge interactions

Abstract: Supramolecular interactions allow fine tuning of the charge of coordination complexes, with concomitant control over size and stability of cyclodextrin-based complex coacervate core micelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…[10][11][12] Examples include the assembly of quasi-onedimensional fibrillar aggregates with tunable kinetic characteristics, hierarchical assemblies, and branched networks such as hydrogels and coacervates. [13][14][15] In addition, supramolecular polymers can be used as modular templates for the assembly of various biomolecules, including nanoparticles, 16,17 nucleic acids, 18,19 and proteins. [20][21][22][23] Recent work has revealed that intracellular signalling pathways heavily rely on the dynamic assembly of higher-order fibril-like aggregates that are structurally well-defined but open-ended and sometimes quasi-infinite.…”
mentioning
confidence: 99%
“…[10][11][12] Examples include the assembly of quasi-onedimensional fibrillar aggregates with tunable kinetic characteristics, hierarchical assemblies, and branched networks such as hydrogels and coacervates. [13][14][15] In addition, supramolecular polymers can be used as modular templates for the assembly of various biomolecules, including nanoparticles, 16,17 nucleic acids, 18,19 and proteins. [20][21][22][23] Recent work has revealed that intracellular signalling pathways heavily rely on the dynamic assembly of higher-order fibril-like aggregates that are structurally well-defined but open-ended and sometimes quasi-infinite.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] These quaternization reactions are, however, often incomplete and thus require thorough analysis in order to determine the exact charge density, which is a crucial parameter when polyelectrolyte complexes are concerned. 26,27 Polystyrene sulfonate is among the easiest accessible strong polyanions, and while it can be synthesized directly from commercially available styrene sulfonate, sulfonation of polystyrene continues to be the most frequently applied route toward this polyelectrolyte. Similar to the previously discussed quaternization reactions, sulfonation of polystyrene is often incomplete as well, and in addition, involves the use of corrosive and toxic reagents.…”
mentioning
confidence: 99%
“…By diluting a micelle sample with deionized water, the Critical Micelle Concentration (CMC) was determined to be around 50 μM Eu(III) ions, comparable with the previous value of Ad-Glu-Ad-based C4Ms (Figures S13). [23] The micelles disassemble upon increasing ionic strength due to screening of the electrostatic charges by salt ions ( Figure S14); [12] the Critical Salt Concentration (CSC) is ca. 30 mM of NaCl, similar to the CSC found for Ad-Glu-Ad-based C4Ms.…”
Section: Resultsmentioning
confidence: 99%
“…As previously demonstrated, six negative charges (per monomeric unit) are not enough to form stable and well-defined coacervate micelles, but rather unstable and non-uniform aggregates. [23] Therefore, the addition of DTT favors the micellar disassembly (Scheme 2, bottom).…”
Section: Redox Response Of Ad-ss-ad-based C4msmentioning
confidence: 99%
See 1 more Smart Citation